Obtaining high thermally conductive materials by pressing from the granulate - Ditts A. A. Aleksander Andreevich; Revva I. B. Inna Borisovna; Pautova Yu. I. Yuliya Igorevna; Pogrebenkov V. M. Valery Matveevich; Nepochatov Yu. K. Yury Kondratjevic; Tarnovsky R. V. Roman Vladimirovich; Galashov E. N. Evgeny Nikolaevich (2015, 2015)
Title screen